From the lockdown to the new normal: An analysis of the limitations to individual mobility in Italy following the Covid-19 crisis - Mauro Caselli; Andrea Fracasso; Sergio Scicchitano (Global Labor Organization (GLO), 2020)
Italy was among the first countries to introduce drastic measures to reduce mobility in order to prevent the diffusion of Covid-19. On March 9, 26 out of 111 provinces were subject to severe limitations on individual mobility between municipalities. One day later, new restrictive measures were introduced in the whole country with no regional distinctions: this continued until June 3 when the limits on movements across regions were eventually lifted. By looking at these watershed moments, this paper explores, for the first time, the impact of the adoption and the removal of restrictive measures on changes in individual mobility in Italy. By using a spatial discontinuity approach, we show that these measures were effective in that they lowered individual mobility by about 7 percentage points relative to what is accounted for by the characteristics of the local population and the disease. The analysis shows, however, that local features played an important role after the travelling bans were lifted: the catching up with pre-Covid-19 patterns has been stronger in those areas where the labour force is relatively less exposed to the risk of contagion and less likely to work from home.
Keywords: I19; O33; 330; Covid-19; lockdown; mobility; risk of contagion